Power and society: a framework for political inquiry - Lasswell, Harold D.; Kaplan,Abraham (New Haven, 1965)
This book contributes to the w wave of interest in the United States in the systematic theory of politics, law, and related social sciences. During the past thirty years political science has underage an "empirical revolution" which has produced many descriptive studies of political parties, pressure groups, public opinion, propaganda, war, and methods. public administration. POWER AN SOCIETY aims to provide a basic frame work for communicating the present postulates, hypotheses, and findings of political science.
Keywords: Political Science